Questionnaire for Impulsive-Compulsive Disorders in Parkinson’s Disease–Rating Scale - Weintraub, Daniel (2011)
Impulse control disorders and related disorders (hobbyism-punding and dopamine dysregulation syndrome) occur in 15% to 20% of Parkinson’s disease (PD) patients. We assessed the validity and reliability of the Questionnaire for Impulsive-Compulsive Disorders in Parkinson’s Disease–Rating Scale (QUIP-RS), a rating scale designed to measure severity of symptoms and support a diagnosis of impulse control disorders and related disorders in PD. A convenience sample of PD patients at a movement disorders clinic self-completed the QUIP-RS and were administered a semistructured diagnostic interview by a blinded trained rater to assess discriminant validity for impulse control disorders (n = 104) and related disorders (n = 77). Subsets of patients were assessed to determine interrater reliability (n = 104), retest reliability (n = 63), and responsiveness to change (n = 29). Adequate cutoff points (both sensitivity and specificity values >80% plus acceptable likelihood ratios) were established for each impulse control disorder and hobbyism-punding. Interrater and retest reliability (intraclass correlation coefficient r) were >0.60 for all disorders. Participants in an impulse control disorder treatment study who experienced full (t = 3.65, P = .004) or partial (t = 2.98, P = .01) response demonstrated significant improvement on the rating scale over time, while nonresponders did not (t = 0.12, P = .91). The QUIP-RS appears to be valid and reliable as a rating scale for impulse control disorders and related disorders in PD. Preliminary results suggest that it can be used to support a diagnosis of these disorders, as well as to monitor changes in symptom severity over time.